The Aegilops tauschii genome reveals multiple impacts of transposons. (December 2017) - Zhao, Guangyao; Zou, Cheng; Li, Kui; Wang, Kai; Li, Tianbao; Gao, Lifeng; Zhang, Xiaoxia; Wang, Hongjin; Yang, Zujun; Liu, Xu; Jiang, Wenkai; Mao, Long; et al.
Abstract Wheat is an important global crop with an extremely large and complex genome that contains more transposable elements (TEs) than any other known crop species. Here, we generated a chromosome-scale, high-quality reference genome ofAegilops tauschii, the donor of the wheat D genome, in which 92.5% sequences have been anchored to chromosomes. Using this assembly, we accurately characterized genic loci, gene expression, pseudogenes, methylation, recombination ratios, microRNAs and especially TEs on chromosomes. In addition to the discovery of a wave of very recent gene duplications, we detected that TEs occurred in about half of the genes, and found that such genes are expressed at lower levels than those without TEs, presumably because of their elevated methylation levels. We mapped all wheat molecular markers and constructed a high-resolution integrated genetic map corresponding to genome sequences, thereby placing previously detected agronomically important genes/quantitative trait loci (QTLs) on theAe. tauschii genome for the first time. The wild grassAegilops tauschii is a wheat progenitor. A high-quality genome sequence, along with methylome and transcriptome data, provides insights on domestication and the effect of transposons, and offers a resource for wheat improvement.